The Potential of Cynodon Dactylon and Lolium Perenne 'Brightstar' as Phytoremediator Agents in Dealing with the Problem of Sea Water Intrusion in the North Coastal Area of Karawang - Rizkiah, Riza; Sewiko, Roni; Pranoto, Aris Kabul; Pasaribu, Roberto Patar; Djari, Anthon Anthonny; Rahman, Abdul; Ismail, R Moh; Handayani, Endy; Luciana, Luciana; Mulyana, Muhammad Agus (Sainteks: Jurnal Sain dan Teknik, 2024)
Sea water intrusion is a process where sea water is mixed with underground water around the coast, causing the ground water to become salty because it is contaminated by sea water which is rich in salt. Sea air that enters the ground causes the air to become unfit for consumption and causes the land to become unproductive for planting. People in the Pakis Jaya area, Karawang face difficulties, especially regarding land use for agricultural activities. This is because the land used for cultivating plants is saline soil with a high salt content. Phytoremediation is a method used to clean air or soil contaminated with pollutants, by using the ability of plants to absorb these substances. Cynodon Dactylon and lolium Perenne Brightstar plants are a type of grass that can be used to reduce high salt levels in the soil because these plants are able to live in places with high salinity and also have the ability to reduce salinity by absorbing chloride ions in it. The methods used in this research consisted of: Sampling Process, Plant Acclimatization Stage, Salinity Concentration Test before and after planting grass in Soil Media. The test results showed that the salt content in the soil before planting was 19.20 dS/m and after planting it was 0.02-0.03 dS/M.